Challenges in Laparoscopic Simple Nephrectomy of Non-functioning Kidneys Due to Urolithiasis - Güner Yıldız; Özcan Kılıç; Ali Furkan Batur; Murat Akand (Journal of Urological Surgery)

(untitled)
Objective:Simple nephrectomies may be challenging owing to the fibrotic and inflammatory processes that extend to the renal hilum and perirenal adipose tissue. This study aimed to investigate the complications of laparoscopic nephrectomies for atrophic kidneys.Materials and Methods:Data of patients who underwent laparoscopic nephrectomy for atrophic kidneys were retrospectively evaluated. Preoperatively, all patients had undergone biochemical examinations, computed tomography and scintigraphic studies. The localisation of the stone, affected side, size of the atrophic kidney and presence of fistula and abscess were evaluated radiologically in the preoperative period. The pathology results of the patients were also assessed.Results:A total of 53 patients were included. Conversion to open surgery was necessary in 3 (6%) patients. Pathology reports of these patients revealed xanthogranulomatous pyelonephritis. Moreover, 10 (19%) patients had Clavien-Dindo score >1. Postoperative fistula or abscess formation was not observed in any patient. None of patients had dialysis or sepsis in the postoperative period. Compared with the preoperative data, postoperative creatinine and blood urea nitrogen values were significantly increased.Conclusion:Although laparoscopic nephrectomy is a gold standard treatment option, especially for atrophic kidney, nephrectomies for xanthogranulomatous pyelonephritis can become challenging even for the most experienced surgeons. Thus, surgeons should be always ready to transition to open surgery and be aware of the occurrences of complications in the perioperative and early postoperative periods.